2020
DOI: 10.1108/pr-01-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model of team resilience: exploring the roles of team sensemaking, team bricolage and task interdependence

Abstract: PurposeThe contemporary organizational environment calls for work team members to be more resilient in the face of likely setbacks, which are routinely experienced at the workplace. In two separate studies of work teams, we examine the impact of team sensemaking on team bricolage and subsequently, on team resilience. These studies further investigate whether task interdependence moderates the mediation of team bricolage for the relationship between team sensemaking and team resilience. In brief, these two stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 131 publications
0
23
0
1
Order By: Relevance
“…Teams with collective resilience have been noted to favorably adapt to challenges (Stoverink, Kirkman, Mistry, & Rosen, 2020). For example, resilient teams have positive qualities like collective optimism and an energetic outlook (Morgan, Fletcher, & Sarkar, 2017), inquisitiveness, and openness to new frontiers (Talat & Riaz, 2020). Team resilience in adaptive form to green‐related challenges will cope effectively to green‐related challenges and challenging the status quo.…”
Section: Clarification Of Concepts and Hypothesis Developmentmentioning
confidence: 99%
“…Teams with collective resilience have been noted to favorably adapt to challenges (Stoverink, Kirkman, Mistry, & Rosen, 2020). For example, resilient teams have positive qualities like collective optimism and an energetic outlook (Morgan, Fletcher, & Sarkar, 2017), inquisitiveness, and openness to new frontiers (Talat & Riaz, 2020). Team resilience in adaptive form to green‐related challenges will cope effectively to green‐related challenges and challenging the status quo.…”
Section: Clarification Of Concepts and Hypothesis Developmentmentioning
confidence: 99%
“…Creating dialogues to discuss challenging situations through strengthening communication channels (Kegelaers et al, 2020 ), is shown to capture more implicit elements in coordinating actions. Talat and Riaz ( 2020 ) suggest utilising team member bricolage as a combination of resources at hand in the team in order to develop the sensemaking of a team. One player elaborates his view on utilising small-sized group structures, explaining his belief in discussion and collaboration while debriefing and planning actions through video-analysis reflections of handling challenging situations:…”
Section: Methodsmentioning
confidence: 99%
“…Different views might be beneficial for developing the sensemaking managing and coordinating the effort of the team by explaining and anticipating situations (Talat and Riaz, 2020 ), but as the player reflection shows, shared understanding needs agreement. In line with the suggestions of Morgan et al ( 2019 ), enablers such as shared vision, encouragement of honest feedback, and distributed responsibility are found to cultivate such mutual trust during difficult periods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations